Counting in Action: On Early Baltic Computational Practises and Their Possible Near Eastern Influence - Barusevičius, Dominykas (Archaeologia Lituana, 2024)
This paper proposes that early Baltic computational practices emerged in action, through gesticulation with clay figurines of various shapes and sizes, and were possibly influenced by the Near Eastern token traditions. To substantiate this hypothesis, the phenomenon of counting in action is examined through considerations of ontological grounds and analysis of relevant archaeological evidence. This reveals that a hylomorphic ontology poses challenges to understanding the phenomenon of counting, as it requires reducing counting to an immanent faculty arising within intelligence. In contrast to this reduction, a relationalistic ontology is suggested, proposing that, despite limitations or contradictions imposed by the participants in the relationship, counting emerges in action through technical gesticulations with things. Building on this relationalistic perspective, the computational nature of Baltic clay figurines is inferred from analogies with Near Eastern material counting tokens, resulting in a typology that includes biconoids, concaves, discs, miniature vessels, spheres, tools, and miscellaneous items. This inference is supported by the important case of biconoid figurines from the Nevieriškės fortified settlement, which serve as direct evidence of their potential computational nature. Additionally, if Baltic clay figurines were indeed used as counting tools influenced by Near Eastern token traditions, this supports the claim that Near Eastern computational prototechnologies could have spread beyond their geographical origins.